An Albanian Case Study On Measuring the Service Quality in An Academic Library - Kola, Blerim (European Journal of Multidisciplinary Studies, 2016)
Purpose – The aim of this study is to measure the perceptions of the Faculty of Economics of Tirana library users as they relate to quality service and to determine how far this library has succeeded in delivering such service to its users. Design/methodology/approach – The research was carried out among the students of the Faculty of Economics of Tirana. A questionnaire was used as the data gathering instrument. The instruments for data collection consisted of structured questions. All the closed ended questions were designed to elicit responses on a five point Likert scale to measure both respondent satisfaction and perception of service quality. Analysis of the collected data made use of the chi-square method. Findings – The results would appear to indicate that Faculty of Economics of Tirana library is not lacking in quality of service. However, we need to note that quality information service is about helping users to define and satisfy their information needs, building their confidence in using information retrieval systems, and making the whole activity of working with library staff a pleasurable experience. To achieve total quality in information service the Faculty of Economics of Tirana library should provide a comprehensive information programme that is predicated on the needs and activities of the users. Originality/value – This article may help those libraries, who are seriously interested to develop user satisfaction and provide better service to the user. This article also suggests some recommendations about increasing the user satisfaction in the library service.
Keywords: Library, Albania, Service Quaulity